Предмет: Алгебра, автор: gxjdguw

Увага! Завдання на фото.

Приложения:

Ответы

Автор ответа: Universalka
0

f(x)=\frac{x^{2}- x}{x+1} \\\\f'(x)=\frac{(x^{2}-x)'*(x+1)-(x^{2}-x)*(x+1)'}{(x+1)^{2} }=\frac{(2x-1)(x+1)-(x^{2}-x) }{(x+1)^{2} } =\frac{2x^{2}+2x-x-1-x^{2}+x}{(x+1)^{2} }=\frac{x^{2}+2x-1 }{(x+1)^{2} }\\\\f'(x_{0})=f'(0)=\frac{0^{2}+2*0-1 }{(0+1)^{2} }=\frac{-1}{1}0-1\\\\f'(x_{0})=f'(-2)=\frac{(-2)^{2}+2*(-2)-1 }{(-2+1)^{2} }=\frac{4-4-1}{(-1)^{2} } =\frac{-1}{1}=-1

Похожие вопросы
Предмет: Математика, автор: evasikyey